DESCRIPTION OF BEHAVIOR RELATED TO SUICIDE IN STUDENTS WHO HAVE EXPERIENCED BULLYING - Mikaela Berliyana Alitani (Sean Institute, 2023)
Suicide-related behaviors are a series of processes that include thoughts about suicide, thoughts of trying to commit suicide, thoughts of suicide, to the realization of suicide attempts. One of the factors that cause Suicide related behaviors is psychological factor. Psychological factors refer to events that cause psychological pain in individuals. Bullying is one of the events that cause psychological pain. This bullying can occur at various levels of school. And the impact can be felt by individuals over a long period. Even until individuals have become students in college. This research provides an overview of Suicide related behaviors on college students who have experienced bullying. This type of research is descriptive with an accidental sampling involving 100 college students, aged 17 to 24 years. The results of this study indicate that students who have experienced bullying have Suicide related behaviors with a high category of 47% and a low category of 53 %. In addition, the results also showed that Suicide related behaviors in female students were higher than that of female students.